The Financial Toxicity Experience of Patients with Colorectal Cancer During Chemotherapy: A Qualitative Study - Yanli Yao; Shijing Zhang; Qun Yu; Xia Zhao; Xinqiong Zhang (Current Oncology)
Background: This study aimed to explore the experience of financial toxicity in patients with colorectal cancer during chemotherapy and to inform the development of targeted interventions. Methods: A descriptive qualitative research method was used to conduct semi-structured interviews with a purposive sample of 15 patients with colorectal cancer undergoing chemotherapy who attended the Department of Medical Oncology of the First Affiliated Hospital of Anhui Medical University from March to June 2024, and the data were organized and analyzed using the Nvivo 11.0 qualitative data analysis software and the thematic analysis method. Results: Four themes were extracted: patients with chemotherapy-stage colorectal cancer bear direct and indirect multifaceted economic pressures, are affected by multidimensional risk factors, which cause multiple adverse outcomes, and cope with financial toxicity in various ways. Conclusions: The experience of financial toxicity in colorectal cancer patients undergoing chemotherapy is presented in a multidimensional format, with multiple causes influencing their financial toxicity. In the future, healthcare professionals should identify patients at high risk for financial toxicity, provide financial toxicity interventions and support, and mitigate their exposure to financial toxicity.